Emotive cities: understanding human perception of urban spaces – a pilot study - Manohar, Lakshmi; Kurukkanari, Chithra (Frontiers in Built Environment, 2026)
Neurourbanism offers new ways to understand how urban environments shape human cognition and emotion, yet empirical studies in rapidly urbanizing regions like South India remain scarce. This pilot study investigates how diverse urban settings in Calicut, Kerala, influence neurophysiological states using mobile EEG technology. Participants navigated urban spaces varying in street enclosure, natural features, and activity levels, with EEG readings analyzed for emotional states including excitement, engagement, interest, relaxation, and stress. Results show significant shifts in these metrics as environments transitioned from busy to calm, narrow to wide, urban to green, and crowded to less occupied. This study is the first to apply mobile EEG in a South Indian context, highlighting the potential for evidence-based urban design to enhance mental wellbeing. Findings underscore the importance of integrating green spaces, optimizing street scale, and promoting walkability in urban planning, with implications for policy and design practice in developing cities.